Teaching Listening Skills Using Films: Implementation and Analysis Towards Students’ Response - Dewi, Bela Noviana (Nurul Jadid University, 2023)
Teaching Arabic has become a big challenge for some teachers, because they face difficulty in explaining the material to students. Therefore, the teacher must be able to choose the appropriate teaching methods so that students do not feel bored and have a great interest in learning Arabic. This study aims to explain the process of using films as a teaching method for listening skill at Dar Al Salam Kontour Institute for Girls, first campus, and their response during the learning process. The researcher used the qualitative approach in this research. Data were collected using observations, interviews, and documentation studies, and then analyzed by observation during learning activities using films. The results of this study are that films can be used as an interesting teaching method for teaching listening skill and make students more enthusiastic with audio and visual groups.